HOW ENGLISH BECOME GLOBAL LANGUAGE: HISTORICAL OVERVIEW - Mamadjanova , Maftuna Uktamovna; Malikova, Gulchehraxon Xasanboy qizi (Educational Research in Universal Sciences, 2023)
The rise of English as a global language has been a remarkable phenomenon in the history of human communication. This article provides a comprehensive historical overview of how English evolved from a regional language to a global lingua franca. It examines the key historical events, socio-political factors, and technological advancements that have contributed to the widespread adoption and dominance of English as a global language. The article also explores the impact of English on world cultures, education, and international communication. By delving into the historical roots of English as a global language, this article seeks to provide valuable insights into the linguistic and cultural dynamics that have shaped the modern world.